Thermogravimetry of ternary cement blends: Effect of different curing methods - Watcharapong Wongkeo (2018)
This study reports the microstructure characteristic and compressive strength of multi-blended cement under different curing methods. Fly ash, ground bottom ash, and undensified silica fume were used to replace part of cement at 50 % by mass. Mortar and paste specimens were cured in air at ambient temperature, water at 25, 40, and 60 C and sealed with plastic sheeting for 28 days. In addition, these specimens were cured in an autoclave for 6, 9, and 12 h. Results indicated that the compressive strength of multi-blended mixes containing silica fume 10 % by mass cured with plastic sealed and cured in water at 25 and 40 C was similar to or higher than the corresponding Portland cement control at 28 day. Moreover, the mixes containing silica fume 10 % by mass cured in water at 60 C had higher compressive strength than Portland cement control. X-ray diffraction and thermogravimetry results confirmed that there was increased pozzolanic reaction with increasing silica fume content which relates to the increasing in strength. For autoclaved curing, the compressive strength of multi-blended cement specimens with silica fume (total of 50 % replacement) was noticeably higher than control Portland cement mix and was highest when autoclaving time was 9 h. X-ray diffraction results showed the pattern of 0.9, 1.1, and 1.4 nm tobermorite crystalline phases as the main product of this curing. Thermogravimetry results showed dehydration of 1.4 nm tobermorite and 1.1 nm tobermorite at about 80-90 and 135-150 C, respectively. Tobermorite (also shown by scanning electron microscope) thereby as a result lead to significant compressive strength improvement in the short time of autoclaved curing. © 2013 Akadémiai Kiadó, Budapest, Hungary.